ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI KUBIS DI DESA PETLENG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Maure, Gerson Hans; Demang, Ferdinan; Mokoni, Orpa (JURNAL AGRIMANSION, 2024)
Cabbage is a leaf vegetable that is quite popular and popular in Indonesia and has high commercial value and prospects. The research was carried out in Peteleng Village, North Central Alor District from March - May 2024. The total sample was 30 people using saturated samples. Data collection was done through direct interviews with respondents, publication of data from the Alor Regency Central Statistics Agency and the Alor Regency Agriculture and Plantation Service. The research aims to analyze the factors that influence farmers' decisions in cabbage farming in Petleng Village, North Central Alor District. The results of the research show that the F test shows that the independent variables income, land area, farming experience and capital have a significant influence on farmers' decisions (Y) and the t test shows that the variables of land area and capital have a positive and insignificant effect on farmers' decisions in carrying out cabbage farming, while the variables income and farming experience have a positive and significant influence on farmers' decisions in carrying out cabbage farming in Petleng Village, Alor Tengah Utara District.